Teamwork in a coronary care unit: facilitating and hindering aspects - Bethania Ferreira Goulart; Silvia Helena Henriques Camelo; Ana Lúcia de Assis Simões; Lucieli Dias Pedreschi Chaves (SciELO, 2016)
Abstract OBJECTIVE To identify, within a multidisciplinary team, the facilitating and hindering aspects for teamwork in a coronary care unit. METHOD A descriptive study, with qualitative and quantitative data, was carried out in the coronary care unit of a public hospital. The study population consisted of professionals working in the unit for at least one year. Those who were on leave or who were not located were excluded. The critical incident technique was used for data collection, by means of semi-structured interviews. For data analysis, content analysis and the critical incident technique were applied. RESULTS Participants were 45 professionals: 29 nursing professionals; 11 physicians; 4 physical therapists; and 1 psychologist. A total of 49 situations (77.6% with negative references); 385 behaviors (54.2% with positive references); and 182 consequences emerged (71.9% with negative references). Positive references facilitate teamwork, whereas negative references hinder it. A collaborative/communicative interprofessional relationship was evidenced as a facilitator; whereas poor collaboration among agents/inadequate management was a hindering aspect. CONCLUSION Despite the prevalence of negative situations and consequences, the emphasis on positive behaviors reveals the efforts the agents make in order to overcome obstacles and carry out teamwork.